Prospective Cohort Study Investigating Polyunsaturated Fatty Acids and Chronic Lung Disease in Preterm Infants - Igawa, Teryn; Gillespie, Tessa C.; Kim, Esther S.; Lee, Lauren J.; Grogan, Tristan; Chu, Alison; Calkins, Kara L. (American Journal of Perinatology, 2025)
Chronic lung disease (CLD) is a complication of prematurity. Studies examining the effects of long-chain polyunsaturated fatty acids (LC-PUFAs) on CLD are conflicting. This study investigated LC-PUFAs in the red blood cell membrane (RBCM) in preterm infants.This prospective observational study included infants with gestational age <32 weeks or birth weight <2 kg and at least one LC-PUFA measurement in the first month of life. Subjects without CLD (CON group) were compared with those with CLD (CLD group) and then by CLD severity.Seventy infants were included (CON n = 29; CLD n = 41). Twenty-six infants had Grade 1 CLD; 12 had Grade 2 CLD; 3 had Grade 3 CLD. When the CLD group was compared with the CON group, the overall mean (95% confidence interval) RBCM% for linoleic acid (LA) was similar (CLD vs. CON 12.5% [11.7–13.4%] vs. 11.2% [10.2–12.3%], p = 0.06) but the overall mean arachidonic acid (ARA) was lower (17.6% [17.1–18.0%] vs. 18.6% [18.1–19.2%], p < 0.01). During weeks 1 to 4, LA% was similar, while ARA% was lower in weeks 2 and 3 (18.8 ± 2.2% vs. 20.0 ± 1.5%, p = 0.05, 16.8 ± 2.0% vs. 18.3 ± 1.6%, p = 0.01). A similar trend was noted when groups were compared by CLD severity. The CLD group had a higher overall mean α-linolenic acid (ALA) compared with the CON group (0.4% [0.3–0.4%] vs. 0.2% [0.2–0.3%], p < 0.01) but no difference in docosahexaenoic acid (DHA; 3.8% [3.4–4.1%] vs. 3.8% [3.4–4.3%], p = 0.80). During weeks 1 to 4, ALA% was higher during week 1 only (0.4 ± 0.3% vs. 0.2 ± 0.1%, p < 0.01), and DHA% was similar for weeks 1 to 4. Results were similar when groups were compared by CLD severity.In this study, low ARA status was associated with CLD.
Keywords: chronic lung disease; long-chain polyunsaturated fatty acids; nutrition; preterm; infant